2012
DOI: 10.1007/s11095-012-0784-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Pharmacokinetic Model for Composite Nanodevices: Effect of Charge and Size on In Vivo Disposition

Abstract: Since the PBPK model can capture the diverse temporal profiles of non-targeted nanoparticles, we propose that when specific binding ligands are lacking, size and charge of nanodevices govern most of their in vivo interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…59 In any case, most, if not all, investigators incorporate partition coefficients into their nano PBPK models. 10,[17][18][19][20][21][22][24][25][26][27] Here, we found that at least in the case of PAA-PEG, PAA, and gold NPs, the biokinetics cannot be accurately described without introducing a P factor and a similar conclusion was reached by Lin et al 25 The exchange of NPs between blood and organs is strongly influenced by the ability to cross the endothelium. This endothelial permeability varies between organs as a result of differences in the degree of fenestration, as well as phagocytic capacity.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…59 In any case, most, if not all, investigators incorporate partition coefficients into their nano PBPK models. 10,[17][18][19][20][21][22][24][25][26][27] Here, we found that at least in the case of PAA-PEG, PAA, and gold NPs, the biokinetics cannot be accurately described without introducing a P factor and a similar conclusion was reached by Lin et al 25 The exchange of NPs between blood and organs is strongly influenced by the ability to cross the endothelium. This endothelial permeability varies between organs as a result of differences in the degree of fenestration, as well as phagocytic capacity.…”
supporting
confidence: 71%
“…However, several investigators have emphasized the importance of corona dynamics and this aspect of modeling needs to be explored further, especially in relationship to alterations in NP partitioning between blood and tissues and the rate of phagocytic uptake with time. 21,23,57 The incorporation of partition coefficients (sometimes referred to as distribution coefficients) into our model can be questioned since, in contrast to small, nonionized molecules, NPs form thermodynamically unstable, nonheterogenous suspensions so that partitioning equilibrium may not be attained. 58 Thus, NPs tend to agglomerate/aggregate, conditions in the body may cause a corona to change with time, and most preparations contain NPs with a range of sizes.…”
mentioning
confidence: 99%
“…Temporal exposure and elimination of five golddendrimer composite nanodevices in mice bearing melanoma was evaluated using a PBPK model (Mager et al, 2012). The authors concluded that, as specific binding ligands were lacking, size and charge of composite nanodevices governed most of their in vivo interactions.…”
Section: Pbpk and Nanotechnology: Current Examplesmentioning
confidence: 99%
“…To obtain the remaining parameter values for AMD, a simplified ''open loop'' model [53,54] consisting of two compartments (blood and one single tissue) was developed. In this ''open loop'' model, the blood kinetics was fixed, and the chemical-specific parameters for each tissue were estimated individually.…”
Section: Model Parametersmentioning
confidence: 99%